Moisture Transport Anomalies over the Danube River Basin during Two Drought Events: A Lagrangian Analysis - Milica Stojanovic; Anita Drumond; Raquel Nieto; Luis Gimeno (Atmosphere, 2017)
In this paper, we provide a Lagrangian analysis of the anomalies in the moisture transport during two important drought events (1989/1990 and 2003) configured over the Danube River Basin (DRB) region. Firstly, we identified the drought episodes that occurred over the DRB in the period of 1980–2014 through the Standardized Precipitation Evapotranspiration Index (SPEI). SPEI was calculated using monthly Climatic Research Unit (CRU) Time-Series (TS) Version 3.23 precipitation and potential evapotranspiration (PET) datasets with a spatial resolution of 0.5 degrees. The monthly SPEI-1 index was applied to identify the drought episodes and their respective indicators, including duration, severity, and intensity. Two significant drought events were selected: 1989/1990 (presenting dry conditions during October 1989–March 1990) and 2003 (presenting dry conditions during April 2003–September 2003). These events were associated with the two most severe SPEI-1 episodes identified over the DRB during 1980–2014. Then, an analysis of anomalies in the moisture transport was conducted in order to verify possible changes in the moisture supply from the climatological sources for the DRB during these episodes. The moisture transport analysis was performed through a Lagrangian approach, which uses the outputs of the FLEXiblePARTicle dispersion model FLEXPART integrated with one of the reanalysis produced by the European Centre for Medium-Range Weather Forecasts (ECMWF): the ECMWF Re-Analysis (ERA)-Interim dataset. The DRB receives moisture from seven different moisture source regions: the North Atlantic Ocean (NATL), North Africa (NAF), the Mediterranean Sea (MED), the Black Sea (BS), the Caspian Sea (CS), the DRB, and Central and Eastern Europe (Rest of Land (RestL)). The analysis of drought events shows that the precipitation and moisture supply from the selected sources weakened mainly during both drought events. Anomalous subsidence and an increased PET also prevailed over the DRB during these SPEI-1 episodes. RestL and MED ...